Soil-geomorphological mapping of Samoylov Island based on UAV imaging - Polyakov, Vyacheslav; Kartoziia, Andrei; Nizamutdinov, Timur; Wang, Wenjuan; Abakumov, Evgeny (Frontiers in Environmental Science, 2022)
Soil mapping is a reliable tool for analyzing the patterns of soil distribution in various parts of the earth's surface. Cryogenic and watershed areas are the most dynamic landscapes with relatively rapid transformation under the influence of climate change and river activity. We proposed a soil-geomorphological map obtained unmanned aerial vehicle (UAV) imaging, classical soil sections, geomorphological observation, and determination of the main chemical parameters of soils. Four types of soils were identified due to their position in the relief and chemical parameters. The dominant soil type on the Samoylov Island is Folic Cryosol (Siltic) (41.1%). The use of high-resolution UAV imaging to construct soil-geomorphological maps is the most relevant method for analyzing soils formed in cryogenic, watershed and mountainous landscapes. The soil-geomorphological maps can be used to analyze the reserves and contents of organic and inorganic components with high accuracy.